DESIGNING AND DEVELOPMENT OF GASTRORETENTIVE MUCOADHESIVE MICROSPHERES OF CEFIXIME TRIHYDRATE USING SPRAY DRYER - CHATURVEDI, PRIYANKA; SONI, PRAKASH KUMAR; PASWAN, SURESH KUMAR (International Journal of Applied Pharmaceutics, 2023)
Objective: Cefixime is a weakly acidic drug primarily absorbed through the stomach and upper intestinal part and has incomplete absorption in lower GIT which leads to its poor bioavailability. The current research work is aimed to develop gastroretentive mucoadhesive microspheres of cefixime to enhance absorption in the stomach. Methods: Cefixime trihydrate mucoadhesive microspheres formulation was developed by spray drying technique and optimized by DoE approach using Box-Behnken design. The independent variables selected in the formulation were HPMC K15M (X1) as carrier polymer, Carbopol 971P (X2) as mucoadhesive polymer and Cefixime trihydrate (X3). The response variables studied were mean particle size (R1), and percent cumulative drug release at different time points (R2-R8). The optimized batch was evaluated for mucoadhesion properties, DSC and SEM analysis. Results: The Ex-vivo test of cefixime microspheres studied on goat intestinal mucosa showed strong mucoadhesion of 82% for an extended period of 6 h. The in vitro drug release studies of microspheres in 0.1 N HCl showed extended release up to 8 h. The DSC thermograph indicated the conversion of the drug from crystalline form to amorphous form following the formation of solid dispersion. SEM analysis reveals the microspheres were spherical and smooth. Conclusion: It is concluded from the above studies that the current formulation has increased gastric residence time and prolonged release for better absorption of the drug, thus, the formulation will have better therapeutic and increased bioavailability.